Negative predictive value of procalcitonin to rule out bacterial respiratory co-infection in critical covid-19 patients. Issue 4 (October 2022) - Carbonell, Raquel; Urgelés, Silvia; Salgado, Melina; Rodríguez, Alejandro; Reyes, Luis Felipe; Fuentes, Yuli V.; Serrano, Cristian C.; Caceres, Eder L.; Bodí, María; Martín-Loeches, Ignacio; Solé-Violán, Jordi; Díaz, Emili; et al.
Highlights: Pandemic due to SARS CoV-2 is in few cases associated with bacterial co-infection. A threshold of procalcitonin <0.3 ng/ml may be helpful to rule out bacterial co-infection, and therefore to reduce antibiotics misuse in the context of COVID-19 pneumonia. Procalcitonin levels on admission are useful to predict prognosis. ABSTRACT: Background: : Procalcitonin (PCT) and C-Reactive Protein (CRP) are useful biomarkers to differentiate bacterial from viral or fungal infections, although the association between them and co-infection or mortality in COVID-19 remains unclear. Methods: : The study represents a retrospective cohort study of patients admitted for COVID-19 pneumonia to 84 ICUs from ten countries between (March 2020-January 2021). Primary outcome was to determine whether PCT or CRP at admission could predict community-acquired bacterial respiratory co-infection (BC) and its added clinical value by determining the best discriminating cut-off values. Secondary outcome was to investigate its association with mortality. To evaluate the main outcome, a binary logistic regression was performed. The area under the curve evaluated diagnostic performance for BC prediction. Results: : 4635 patients were included, 7.6% fulfilled BC diagnosis. PCT (0.25[IQR 0.1-0.7] versus 0.20[IQR 0.1-0.5]ng/mL, p<0.001) and CRP (14.8[IQR 8.2-23.8] versus 13.3 [7-21.7]mg/dL, p=0.01) were higher in BC group. Neither PCT nor CRP were independently associated with BC and both had a poor ability to predict BC (AUC for PCT 0.56, for CRP 0.54). Baseline values of PCT<0.3ng/mL, could be helpful to rule out BC (negative predictive value 91.1%) and PCT≥0.50ng/mL was associated with ICU mortality (OR 1.5, p<0.001). Conclusions: : These biomarkers at ICU admission led to a poor ability to predict BC among patients with COVID-19 pneumonia. Baseline values of PCT<0.3ng/mL may be useful to rule out BC, providing clinicians a valuable tool to guide antibiotic stewardship and allowing the unjustified overuse of antibiotics observed during the pandemic, additionally PCT≥0.50ng/mL might predict worsening outcomes.